PENGARUH REWARD DAN PUNISHMENT TERHADAP KINERJA KARYAWAN PADA PT PLN (PERSERO) UNIT PELAKSANA PELAYANAN PELANGGAN (UP3) BOGOR - Sigit Purnomo (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2021)
This study aims to determine the "Effect of Reward and Punishment on Employee Performance at PT PLN (Persero) Customer Service Implementation Unit (UP3) Bogor". The methods of analysis used are descriptive analysis methods and quantitative analysis methods. The data collection method is a questionnaire. The population in this study was employees at PT PLN (Persero) Customer Service Implementation Unit (UP3) Bogor from all employees as many as 105 people to 83 people using slovin formula.Based on the result of the t test with the calculated t value on the reward variable of 2,701 greater than the table t of 1,990 with a probability of t being sig 0.008 is less than the significance limit of 0.05. Based on this value, reward variables have a positive and significant effect on performance variables. In punishment variables of 5,550 greater than table t of 1,990 with a probability of t being sig 0.000 smaller than the significance limit of 0.05, punishment variables partially have a positive and significant influence on performance variables. Based on the results of the F test, the Fhitung value of 59,666 > 3.11 with a sig of 0.000 <? 0.05, indicating Ho was rejected and Ha accepted, meaning reward and punishment simultaneously positively and significantly affect performance variables. The result of the determinant coefficient (R2) is 0.774 meaning that the reward and punishment variables have a strong relationship to performance. Adjusted R Square of 0.599 means a 59.9% improvement in employee performance at PT PLN (Persero) Customer Service Implementation Unit (UP3) Bogor can be explained by reward and punishment variables, while the remaining 41.1% can be explained by other variables not studied in this study.